Admission Cell Free DNA as a Prognostic Factor in Burns: Quantification by Use of a Direct Rapid Fluorometric Technique. (19th June 2014) - Shoham, Yaron; Krieger, Yuval; Perry, Zvi H.; Shaked, Gad; Bogdanov-Berezovsky, Alexander; Silberstein, Eldad; Sagi, Amiram; Douvdevani, Amos
Abstract : Background . Despite great advances in the treatment of burn patients, useful prognostic markers are sparse. During the past years there has been increasing interest in circulating plasma cell free DNA as a potential marker for tissue injury. We have developed a rapid direct fluorescent assay for cell free DNA quantification that allows obtaining accurate, fast, and inexpensive measurements. Objective . To use this technique for measuring plasma cell free DNA levels in burn patients and to further explore the use of cell free DNA as a potential marker of patient outcome in burns. Methods . Cell free DNA levels obtained from 14 burn victims within 6 hours of injury and 14 healthy controls were quantified by a direct rapid fluorometric assay. Results . Patient admission cell free DNA levels were significantly elevated compared with that of controls (1797 ± 1523 ng/mL versus 374 ± 245 ng/mL, P = 0.004 ). There are statistically significant correlations between cell free DNA admission levels and burn degree (Spearman's correlation = 0.78, P = 0.001 ), total body surface area (Spearman's correlation = 0.61, P = 0.02 ), and total burn volume (Spearman's correlation = 0.64, P = 0.014 ). Conclusions . Admission cell free DNA levels can serve as a prognostic factor in burns and future routine use can be made possible by use of our direct rapid fluorometric assay.